Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C.L. Koch, 1837 - Sankaran1, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2017)
The genus Zoica Simon, 1898 comprises the smallest members of the family Lycosidae (Lehtinen & Hippa 1979; Framenau et al. 2009) and all the members are vagrant (Lehtinen & Hippa 1979). The genus was revised by Lehtinen & Hippa (1979) and currently has 12 described species (World Spider Catalog 2017). The species Zoica puellula (Simon, 1898) was based on an unspecified number of female specimens from Sri Lanka, and its original description (Simon 1898) is inadequate and lacks illustrations. The male and female genitalia of this species were subsequently illustrated several times (Roewer 1960; Lehtinen & Hippa 1979; Tikader & Malhotra 1980); however these illustrations are insufficient for proper identification and the internal female genitalia of this species have not been illustrated. Additionally, Tikader and Malhotra (1980) inferred the presence of Z. puellula in India from records of this species in Sri Lanka, but it has not yet been found in India. Here we redescribe Z. puellula based on the type material and newly collected specimens and extend its known geographic distribution to India. We also remove Zoica harduarae (Biswas & Roy, 2008), which was described from India, from the genus.